Das Securities Market Programme: Viele Vorteile für den Euroraum - Franz Nauschnigg (Wirtschaftsdienst, 2018)
Durch das Securities Market Programme (SMP) des Eurosystems von 2010 bis 2012 haben alle gewonnen: Das Eurosystem, da durch das SMP die Fragmentierung der Anleihenmärkte des Euroraums verringert und die Transmission der Geldpolitik verbessert werden konnte. Alle Euroländer, da sie Zusatzgewinne ihrer Notenbanken erhielten. Das Marktversagen auf den Finanzmärkten wurde teilweise korrigiert. Die vergangenen und zukünftigen SMP-Gewinne könnten für eine Fiskalkapazität des Euroraums verwendet werden. – – The Eurosystem's Securities Market Programme (SMP,) the purchase of government bonds of euro area countries strongly affected by the crisis, started in 2010 and ended in 2012. The SMP benefited all parties concerned - the Eurosystem, all euro area countries and the crisis countries. The positive experience with the SMP can be replicated in the private sector with the creation of an exchangetraded fund (ETF), a Smart Beta ETF - SMP Fund. Like the SMP, the SMP Fund would buy government bonds, according to the ECB capital key. As an ETF, the SMP Fund would have low costs. Profi ts above the German Bund benchmark would be shared: 80% to investors, 10% to the SMP Fund and 10% to advisers who recommend the purchase. The related risks would be reduced by the diversifi cation of the SMP Fund, the financing mechanisms of the euro area, especially the European Stability Mechanism (ESM), the Outright Monetary Transactions (OMT) and the banking union. The SMP Fund could support the euro area fi scal capacity and the EU capital markets union. Past and future SMP profits create a fiscal capacity for the euro area with an initial amount of 50 billion Euro.
Keywords: G15; G01; E52; F45; 330